(untitled) (Acta Scientiarum. Health Sciences, 2025)
This study aimed to examine the impact of the parent-child relationship on the duration of technological device use among preschool-aged children. Designed as a cross-sectional analytical study, it was conducted with parents of children aged 3–6 years attending kindergartens and preschools in a district located in the western part of Turkey. The study population consisted of 265 parents, and 263 parents who consented to participate formed the study sample. The sample size was determined using the G*Power analysis program. Data were collected through the Socio-Demographic Characteristics Form, the Parent-Child Relationship Form, and the Technological Device Usage Form. Statistical analyses were performed using the Kruskal-Wallis and Mann-Whitney U tests.The results revealed a significant association between parental education levels and the duration of children’s device use. It was observed that children whose parents had lower educational levels spent more time using technological devices. Additionally, children whose fathers were laborers had longer screen times compared to those whose fathers were civil servants. The study also found that children are exposed to technological devices at an early age and spend a considerable amount of time using them. These patterns varied depending on the socio-demographic characteristics of the parents. Furthermore, establishing clear rules regarding device use was found to be an effective strategy in reducing excessive screen time. In conclusion, parental characteristics significantly influence preschool children’s use of technological devices. It is recommended that educational programs for parents be expanded, and awareness-raising activities on digital media literacy be implemented to support healthier technology use among young children.